TECHNICAL THINKING AND GEOMETRIC IMAGINATION - BEISETZER, Peter (Trends in education, 2021)
Geometric imagination is a unique ability and a significant prerequisite to performing numerous tasks in engineering professional practice. Therefore, intentional development of geometric imagination shall be incorporated into the system of technical thinking development. The primary focus is on the conceptual and systematic application of the educational model reflecting the findings about the actual level of geometric imagination of learners. Thus, the above-mentioned gave rise to the initiative to provide pedagogical professional practice with recommendations leading to the innovation of intentional development of geometric imagination within the teaching process of a subject Engineering. The proposed solution is supported by the metacognitive strategy employed to learners´ self-directed work and verified by the pedagogical experiment.
Keywords: development of geometric imagination; worksheets; metacognitive strategy; research on geometric imagination